1991
DOI: 10.1007/bf01041373
|View full text |Cite
|
Sign up to set email alerts
|

The role of lysosomes in hyaline droplet nephropathy induced by a variety of pharmacological agents in the male rat

Abstract: The male rat is prone to hyaline droplet formation in renal proximal tubular cells. Several unrelated pharmaceutical agents exacerbate the formation and accumulation of these droplets. Where the loading of the proximal tubular cells is marked it gives rise to increased cell turnover and a hyaline droplet nephropathy develops. Cytochemical procedures, have confirmed that this accumulation of hyaline droplets represents an increase in the size and number of secondary lysosomes involved in protein uptake and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…5-II). As denoted earlier, α2u-globulin is a prominent male rat urinary protein which is nearly exclusively degraded in renal lysosomes (Read 1991). As expected, α2u-globulin accumulations were highly prominent in the cytosol of both control and propiverine-treated male rats (Fig.…”
Section: Effects Of Propiverine On Degradation Pathwayssupporting
confidence: 78%
See 1 more Smart Citation
“…5-II). As denoted earlier, α2u-globulin is a prominent male rat urinary protein which is nearly exclusively degraded in renal lysosomes (Read 1991). As expected, α2u-globulin accumulations were highly prominent in the cytosol of both control and propiverine-treated male rats (Fig.…”
Section: Effects Of Propiverine On Degradation Pathwayssupporting
confidence: 78%
“…Of note, the analogous mouse urinary protein (MUP) does not bind the α2u-binding compounds nor does it accumulate in the renal proximal tubules of mice (Dietrich and Rasonyi 1995), reminiscent of the situation described for the species-specific propiverine-induced rDAAO accumulation. Similar to rDAAO but more accentuated, α2u-globulin leads to renal protein overload already under normal physiological conditions (Read 1991;Shimoyama et al 2014). However, while reduced enzymatic metabolism of α2u-globulin exacerbates only the accumulation in the lysosomes of the renal proximal tubules, exacerbated propiverine-induced rDAAO accumulation occurs in the cytosol and the nuclei of the renal proximal tubules (Cuervo et al 1999;Dietrich et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, taking into account the basic and lipophilic properties of the molecule of LTG together with the carrier specificity of this protein for lipophilic ligands, it can be suggested that LTG, when bounded to the α ‐2U‐globulin, makes it more resistant to hydrolysis and/or, when accumulated in the lysosomes, has a direct inhibitory effect on lysosomal function. This reduction of the proteolytic breakdown of α ‐2U‐globulin occurs in the proximal tubule lysosomes, which are located in the cortical region of the kidney [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…In the male rat, besides a good distribution of the antiepileptic drug through all organs and tissues, an accumulation of LTG in the kidneys was observed [5]. This accumulation was attributed to alterations in the renal handling of α ‐2U‐globulin in this species and gender [6,7]. It was suggested that this effect could partly explain the maintenance of LTG serum concentrations over a long period of time [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hyaline droplet nephropathy (also called α 2 -microglobulin nephropathy), which occurs after exposure to a variety of aliphatic, alicyclic, or aromatic compounds (ie, hydrocarbons), is associated with acute kidney injury and the possibility of renal tubular carcinogenesis during recovery. 94 The hyaline droplets that form inside tubular cells are actually lysosomes with a high concentration of α 2 -microglobulin. Exposure to hydrocarbons induces increased lysosomal LAMP-2A, presumably by inducing oxidative stress.…”
Section: Significance Of Cmamentioning
confidence: 99%